2004
DOI: 10.1111/j.1440-1827.2004.01673.x
|View full text |Cite
|
Sign up to set email alerts
|

Anal canal neuroendocrine carcinoma with Pagetoid extension

Abstract: A case of anal canal neuroendocrine carcinoma with Pagetoid intraepithelial extension is presented. An 80-year-old man was admitted to hospital with a complaint of pain in the anorectal region. Clinical examination revealed a hard and fixed mass in the anal canal, and subsequent biopsy of the lesion showed it to be a carcinoma. The surgically resected specimen showed a solid tumor measuring 3.4 x 3.2 cm within the area from the surgical anal canal to the anatomical anal canal. Tumor cells proliferated predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…reviewed a series of gastrointestinal NECs and suggested that NECs arising in the squamous‐lined parts of the gastrointestinal tract, including the esophagus and anal canal, are mostly small‐cell type, whereas large‐cell type NECs are more prevalent in glandular mucosa‐lined areas 6 . In agreement with this study, the majority of previously reported anal canal NECs were small‐cell type 1,3 …”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…reviewed a series of gastrointestinal NECs and suggested that NECs arising in the squamous‐lined parts of the gastrointestinal tract, including the esophagus and anal canal, are mostly small‐cell type, whereas large‐cell type NECs are more prevalent in glandular mucosa‐lined areas 6 . In agreement with this study, the majority of previously reported anal canal NECs were small‐cell type 1,3 …”
Section: Introductionsupporting
confidence: 81%
“…Neuroendocrine carcinoma (NEC) of the anal canal is quite rare, and detailed analyses have been mostly available as isolated case reports 1–3 . Similar to NECs of other gastrointestinal tract organs, anal canal NEC is regarded as a highly aggressive tumor 1,2,4 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations